Unemployment and non-employment in interwar Britain - Butchart, E (University of Oxford, 1997)
Britain already had a serious unemployment problem in the 1920s, but the situation worsened markedly after 1929. We investigate the cause of the higher rates of unemployment experienced throughout the 1930s. The most obvious explanation, that aggregate demand was weaker in the aftermath of the Great Depression, does not stand up to close scrutiny. An alternative explanation is that the emergence of long-term unemployment generated 'hysteresis' effects which enervated the market-clearing mechanism. Although we find that the duration composition of unemployment statistically significantly influenced wage determination we note that real wage growth between 1932-39 was modest. It was not the case that the fruits of economic recovery fed through to wages at the expense of jobs. Instead, we highlight important movements in the labour participation rate over the course of the interwar period. The participation rate declined sharply in the early 1920s, but subsequently recovered. The non-employment rate - the fraction of those of working age who are not in work - consequently paints a different picture of the interwar period than the unemployment rate. In particular, the 1930s do not emerge as having had a more serious problem of joblessness than the 1920s. Hence we tentatively conclude that unemployment was higher during the 1930s largely because the unemployment rate was becoming a more accurate measure of joblessness.